2022
DOI: 10.1186/s12962-022-00354-3
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of pharmacological therapies for people with Alzheimer’s disease and other dementias: a systematic review and meta-analysis

Abstract: Objectives This study aims to synthesize the empirical economic evidence of pharmaceutical therapies for people with dementia. Study design Systematic review and meta-analysis. Literature evaluating the costs and effects of drug therapies for dementia was indexed until December 2021. Quality of study was assessed using the Cochrane Risk of Bias Tool and Consensus on Health Economic Criteria list. Cost data were standardized to 2020 US dollars and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Many economic evaluations on pharmacotherapy in patients with cognitive deficits have compared a treatment of interest with placebo or no treatment control group. 70 , 71 , 72 , 73 , 74 , 75 In future, further research is needed to compare the QoL and cost of JDH with other Korean Medicine, CAM intervention, and Western medicine treatment as well.…”
Section: Discussionmentioning
confidence: 99%
“…Many economic evaluations on pharmacotherapy in patients with cognitive deficits have compared a treatment of interest with placebo or no treatment control group. 70 , 71 , 72 , 73 , 74 , 75 In future, further research is needed to compare the QoL and cost of JDH with other Korean Medicine, CAM intervention, and Western medicine treatment as well.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence from a complex trial which shows that continued treatment with donepezil for people with moderate-to-severe Alzheimer's disease is highly cost-effective in achieving cognitive, functioning and QALY outcomes (Knapp et al, 2017). A recent systematic review and meta-analysis of ten studies of pharmacological therapies concluded that acetylcholinesterase inhibitors and memantine are cost-effective and may be cost-saving (Huo et al, 2022), but cautioned that more rigourous evidence from studies without industrial support is needed.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Despite the important roles of economic evidence, their use in decision-making remains limited. We outline below some examples to illustrate – as noted in several recent systematic reviews and meta-analyses (Huo et al, 2021a, 2021b, 2022; Walsh et al, 2022) – the current lack of economic evidence to support informed decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Huo et al conducted a systematic review of the cost-effectiveness of pharmacotherapy in persons with dementia [ 68 ]. They concluded that neither antipsychotics nor antidepressants, which are commonly used to treat neuropsychiatric symptoms of dementia, were associated with lower healthcare cost.…”
Section: Associations Of Adverse Effects Of Antipsychotic Medications...mentioning
confidence: 99%